Challenges and coping strategies of nursing interns in training for nationwide medical technical skills competition: a qualitative descriptive study - Zhongchen Luo; Qing Wang; Jie Li; Hongli Chen; Hong Li; Keyan Xue; Jiao Tang (BMC Nursing)
Abstract Background Nursing technical skill competitions have proven to be an effective and efficient method for enhancing both learning and teaching within the field. Investigating the obstacles encountered by participants and their strategies for overcoming these challenges is crucial for refining preparation training strategies and daily pedagogical practices. The aim of this study was to examine the challenges and coping strategies of nursing interns as they prepare for the National Medical Technical Skills Competition for College Students in China. Methods A descriptive qualitative study using face-to-face semistructured interviews was conducted. Results Identified challenges included (1) managing training workload and recovery time; (2) a lack of knowledge application and integration abilities; (3) inconsistent training standards affecting training progress; (4) cohesion negatively impacted by an adverse team climate; (5) difficulty in balancing training, academics, and job hunting; (6) emotional resilience and stress regulation; and (7) motivation maintenance. Coping strategies encompassed (1) effectively arranging training content and duration, (2) adopting innovative training approaches and teaching methods, (3) aligning the frequency and difficulty of training assessments with students’ current abilities, (4) enhancing the professional practice and teaching skills of trainers, and (5) pre-selecting contestants based on their characteristics and professional capacity. Conclusion Nursing interns encounter numerous challenges while preparing for the national medical skills competition. It is crucial to create a well-organized training schedule, address negative emotions, provide timely psychological support and establish a high-caliber competition training team to enhancing training effectiveness. Additionally, implementing comprehensive reforms in nursing education teaching methodologies is vital for improving the professional competence of student interns, particularly in strengthening their clinical decision-making skills for analyzing and resolving nursing issues in specific clinical settings. Clinical trial number Not applicable.